LEGAL ANALYSIS OF CRIMINAL RESPONSIBILITY FOR PERPETRATORS OF DRUG CRIMES BASED ON JUSTICE (Decision Study Number: 463/Pid.Sus/2023/PN Smg) - Akbar, Mochamad Rafly; Alia Maerani, Ira (Jurnal Hukum Khaira Ummah, 2024)
Transnational drug crimes are carried out using sophisticated modus operandi and technology, including securing the proceeds of drug crimes. The development of the quality of drug crimes has become a very serious threat to human life. This thesis aims to study and analyze: First, the judge's considerations in sentencing perpetrators of drug crimes based on justice. Second, how is the criminal responsibility for perpetrators of drug crimes based on justice. This assessment is carried out objectively and subjectively. The approach method used is normative juridical, namely a library law study carried out by examining library materials or secondary data alone using deductive thinking methods. The writing specifications use descriptive analysis, the sources and types of data used are secondary data. The method of data collection by collecting data using secondary data collection methods. The problem is analyzed using the theory of criminal responsibility, the theory of punishment and the theory of justice. Criminal responsibility basically lies in the perpetrator where in its provisions every act must be accountable except for provisions that have been regulated in laws and regulations that harm others. Fulfillment of the requirements for criminal responsibility for Decision Number 463/Pid.Sus/2023/PN Smg. Thus, the defendant can be held criminally responsible for the crime of narcotics which is an intermediary in the sale and purchase of class I narcotics, the judge in sentencing the defendant chose imprisonment and a fine, namely imposing a sentence on the Defendant therefore with imprisonment for 5 (five) years and 10 (ten) months and a fine of Rp. 1,000,000,000, - (one billion rupiah) with the provision that if the fine is not paid, it will be replaced with 4 (four) months in prison. Both criminal sanctions, both imprisonment and fines, were imposed by the judge because in Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics.